The role of groundwater in achieving water security and approaches to its governance - Karen, Villholt, (2017)
Groundwater is integral to water security. It is the largest store of unfrozen freshwater on earth, and it serves almost half of the global population for basic water needs. In addition, it contributes more than 40% of the irrigation water globally. Groundwater also secures critical ecosystems and ecosystem services, on which people and the environment depend. This paper gives an overview of the significance of groundwater and the critical interlinkages in the Water–Food–Energy–Climate–Environment nexus. It also discusses how opportunities for bringing in groundwater as part of the solutions to water security at various levels are often missed out. Examples are given of how research can contribute to moving forward to ensure that groundwater plays a stronger role in achieving the SDGs. Realizing that sustainable groundwater development, use and management hinges on conscious and pro-active governance, the presentation gives an highlight of the upcoming book on Advances in Groundwater Governance. Finally, some recent developments in terms of developing global platforms and initiative to work across disciplines, sectors and levels and geographic boundaries to address groundwater management challenges are presented, including GRIPP, the Groundwater Solutions Initiative for Policy and Practice and the Working Group on Groundwater Management under the Sustainable Water Future Program. These initiatives are emerging with strong buy-in from stakeholders at various levels, from local to global.